Assessing the Readiness of Early Childhood Teachers to Facilitate Inclusive Classes - Nisa, Khaerun; Pandu Wijaya, Riko; Ermawati; Putri Lestari Tri; Tjalla, Awaluddin; Dwiutami Wahyuni, Lussy (Universitas Pendidikan Ganesha, 2023)
Every child has the right to receive education tailored to their needs, including those with special needs. Many teachers still need help designing learning activities for inclusion classes. This research aims to analyze the readiness of PAUD teachers to hold inclusive classes. This research uses a quantitative descriptive method with a survey approach. The subjects of this research were 50 PAUD teachers. The method used to collect data was a questionnaire with the help of Google Forms. The data collection instrument is a questionnaire. The questionnaire consists of five aspects and 42 statements, measured using a Likert scale. The data analysis technique is quantitative descriptive analysis. The research results show that most PAUD teachers understand the concept of inclusive education, although some require improvement through training. However, teachers' awareness of the importance of inclusive education needs to be appreciated. Despite the transition's uncertainty, ECCE teachers demonstrate readiness to adopt inclusive practices. The success of inclusive education requires systematic support that includes collaboration, training, and strategic approaches to overcome challenges and guide PAUD teachers toward success in implementing inclusive education. This research implies that PAUD teachers' readiness to facilitate inclusive classes is critical. This readiness is essential to create enjoyable learning activities.